HSP90, HSPA8, HIF-1 alpha and HSP70-2 polymorphisms in breast cancer: a case-control study. - Zagouri, F.; Sergentanis, T.N.; Gazouli, M.; Tsigginou, A.; Dimitrakakis, C.; Papaspyrou, I.; Eleutherakis-Papaiakovou, E.; Chrysikos, D.; Theodoropoulos, G.; Zografos, G.C.; Antsaklis, A.; Dimopoulos, A.M.; et al. (Molecular biology reports, 2012)
This case control study aims to investigate the role of HSP90 Gln488His (C > G), HSP70-2 P1/P2, HIF-1 alpha C1772T and HSPA8 intronic 1541-1542delGT polymorphisms as potential risk factors and/or prognostic markers for breast cancer. 113 consecutive incident cases of histologically confirmed ductal breast cancer and 124 healthy cases were recruited. The above mentioned polymorphisms were genotyped; multivariate logistic regression was performed. HSP90 GG (His/His) genotype was associated with elevated breast cancer risk. Similarly, the allele dose-response model pointed to increase in breast cancer risk per G allele. HSP70-2 P1/P2, HSPA8 intronic 1541-1542delGT and HIF-1 alpha polymorphisms were not associated with breast cancer risk, as evidenced by the dose-response allele models. The positive association between HSP90 G allele and breast cancer risk seemed to pertain to both premenopausal and postmenopausal women. With respect to survival analysis, none of the aforementioned polymorphisms was associated with either disease-free survival or overall survival. HSP90α Gln488His polymorphism seems to be a risk factor for breast cancer. On the other hand, our study did not point to excess risk conferred by HSPA8 1541-1542delGT, Hsp70-2 P1/P2 and HIF-1α C1772T.